(untitled) - Ozawa, Hiromu (Tokyo, Japan, 2020)
The Kidai Shōran is a magnificent painted Japanese scroll, an artistic rendering of one of the most iconic streets of Edo at the beginning of the nineteenth century.
Keywords: Cầu,Bridges; Nhật Bản,Japan